Toba na sae : sejarah lembaga sosial politik abad XIII-XX - Situmorang, Sitor, 1923-; Situmorang, Sitor, 1923-; Situmorang, Sitor, 1923- (Jakarta : Komunitas Bambu, 2004)
History of socioculture of Batak Toba, an ethnic group of North Sumatra, and the struggle of Guru Somalaing against the Dutch colonial in Tapanuli in 13th-20th century
Gabungan dari dua buku karya Sitor Situnorang yang pernah diterbitkan jaitu, Toba na sae (Sinar Harapan, 1993) dan Guru Somalaing dan Modigliani, utusan Raja Roma ... (Grafindo Mukti, 1993) dengan sejumlah tambahan dan perbaikan : P. [xi]
Bibliografi : p. [491]-495
Keywords: Pardede, Somalaing; Toba-Batak (Indonesian people) -- History; Toba-Batak (Indonesian people) -- Social life and customs; Tapanuli Utara (Indonesia) -- History